2011
DOI: 10.1161/circimaging.109.929901
|View full text |Cite
|
Sign up to set email alerts
|

Association Between High-Sensitivity C-Reactive Protein and Coronary Plaque Subtypes Assessed by 64-Slice Coronary Computed Tomography Angiography in an Asymptomatic Population

Abstract: Background-Elevated levels of C-reactive protein (CRP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
4
22
2
1
Order By: Relevance
“…The data from Rubin et al 15 confirm and extend observations from earlier investigations that demonstrated that noncalcified lesions are more likely than calcified lesions to rupture and cause clinical events, that imaging techniques can be used to detect such lesions, and that it is these vulnerable lesions that correlate best with elevated inflammatory biomarker levels. 16 -19 The current data also directly confirm work from Hausleiter and colleagues 20 who showed in a similar, but smaller analysis of intermediate-risk individuals that those with noncalcified vulnerable plaques have significantly higher levels of hsCRP.…”
Section: Article See P 201supporting
confidence: 78%
See 3 more Smart Citations
“…The data from Rubin et al 15 confirm and extend observations from earlier investigations that demonstrated that noncalcified lesions are more likely than calcified lesions to rupture and cause clinical events, that imaging techniques can be used to detect such lesions, and that it is these vulnerable lesions that correlate best with elevated inflammatory biomarker levels. 16 -19 The current data also directly confirm work from Hausleiter and colleagues 20 who showed in a similar, but smaller analysis of intermediate-risk individuals that those with noncalcified vulnerable plaques have significantly higher levels of hsCRP.…”
Section: Article See P 201supporting
confidence: 78%
“…The use of inflammatory biomarker screening in the design of these trials will help to identify a population with a persistent inflammatory response that is most likely to benefit from antiinflammatory therapies and to exclude from randomization patients without a persistent inflammatory response and, thus, a reduced exposure risk among those least likely to benefit. As confirmed in the current study by Rubin and colleagues, 15 this biomarker screening strategy also will increase the likelihood of enrolling patients with vulnerable plaques while reducing the likelihood of enrolling those with heavily calcified lesions unlikely to rupture and less prone to sudden vessel occlusion.…”
Section: Article See P 201supporting
confidence: 53%
See 2 more Smart Citations
“…Smoking is known to increase an inflammatory response which is an essential component in the onset and evolution of atherosclerosis. Several studies have demonstrated a consistent relationship between CRP as a non-specific inflammatory burden indicator and cardiovascular events [28,29]. Although further study of clinical outcomes according to the smoking status is needed, our study indicates that smoking exposure could be related to the inflammatory response for atherosclerosis.…”
Section: Discussionsupporting
confidence: 52%